Spectral Absorbance of Dye Indicator and Liquid-Liquid Interactions - N. Modi, Ashvin.; Desai, C.M. (Asian Journal of Chemistry, 2010)
Molecular interactions have been investigated in binary mixturesof hexane or heptane with CCI4, CHCI3 or CH2CI2 using dye indicators.